The Canadian Taxi Wars, 1925–1950 - Davis, Donald (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1998)
Between 1925 and 1950 most Canadian cities experienced a taxi war during which fares and drivers' incomes plummeted. These wars had their origin in the low barriers to entry into the industry, as it became clear in the late 1920's that motor cabs did not need private concessions, special-built cabs, telephone switchboards and taximeters to make a profit. The older firms that had made these investments were able by 1950 to persuade the larger Canadian cities — including Winnipeg and Vancouver, the two featured here — to introduce the present regulatory regime. The imposition of uniform fares, of taximeters, of minimum wages, of liability insurance, as well as limits on entry into the industry (through the medallion system) ended the taxi wars. The industry thereafter operated in a less chaotic, more ethical way. Yet the new regime also reduced the industry's flexibility, making it less helpful in moving the urban masses.